The Network Origins of Economic Growth - Georg Dürnecker; Moritz Meyer; Fernando Vega-Redondo (University of Mannheim, Department of Economics, 2014)
In this paper, we propose a new approach to represent a country's outward orientation. Prior work mostly uses indicators of aggregate trade intensity, trade policy or trade restrictiveness. Our approach offers a broader perspective as it measures a country's level of integration not only by its set of direct trade connections with the rest of the world but also through the full architecture of its second, third, and all other higher-order connections. We apply our methodology to a sample of 167 countries spanning the period from 1962 to 2009 and perform a Bayesian modelaveraging analysis on the determinants of growth. We find a prominent positive effect of integration on a country's level of per capita income, while the aforementioned traditional measures of outward orientation display only a secondary, largely insignificant, weight. This, we argue, highlights the network basis of economic growth and adds a novel perspective to the notion of economic openness. We also perform several sensitivity checks and conclude that our baseline findings are extremely robust to different data input and alternative assumptions about the computation of country integration.
urn:nbn:de:bsz:180-madoc-354839
Keywords: C11; D85; F15; F63; O40; 330; Globalization; Trade Integration; Economic Growth; Network Analysis; Dynamic Panel Model; Bayesian Model Averaging